Lagrangian pathways connecting the Weddell and Bellingshausen Seas - Bezhenar, Roman; Maderich, Vladimir; Brovchenko, Igor; Boeira Dias, Fabio; Äijälä, Cecilia; Uotila, Petteri (Ukrainian Antarctic Journal, 2024)
This study assesses the connectivity of currents around the Antarctic Peninsula and identifies the structure of flows carrying virtual particles from the Eastern to Western Antarctic Peninsula continental shelves. We use circulation data for the Weddell and Bellingshausen Seas from the Whole Antarctica Ocean Model to obtain and analyse particle trajectories using the Probably A Really Computationally Efficient Lagrangian Simulator (Parcels) model. The software included the main Parcels kernels and a previously developed kernel that ensures the conservation of the number of particles during flow around irregularities in the bottom relief and the lower edge of ice shelves. We also developed a kernel to simulate convection in the ocean’s upper mixed layer. Around 170 000 virtual particles were released at a depth of 10 m during a year with a spatial step of 1° in two shelf and slope sectors in the southern Weddell Sea where the depth is less than 1500 m. The first sector covers the shelf area between 71°S and 77°S adjacent to the Filchner-Ronne Ice Shelf. The second sector covers the shelf area between 70°S and 65°S adjacent to the Larsen Ice Shelf. The pathways of water masses were characterised by the percentage of particles that visit each 10 × 10 km grid cell at least once in a modelling period of 20 years. 21% of particles cross 58°W (tip of the Antarctic Peninsula), while 70% of particles turn northeast. The smaller sector, adjacent to the Larsen Ice Shelf, is the main source of particles transferred to the Bellingshausen Sea (51%). In contrast, particles released in the larger sector were mostly transported to the northeast (75%). Only 3.4% of the released particles were transported to the west of 80°W, while the Amundsen Sea (105°W) was reached only by 0.1% of released particles. That indicates a virtual lack of circulation connectivity between the Weddell and the Amundsen Seas.